STRATEGI KOMUNIKASI GURU DALAM MENGASAH KEMAMPUAN KOMUNIKASI PADA MURID TUNARUNGU (Studi Kasus pada SDLB-B YPTB Malang) - Wisadirana, Darsono; Safitri, Reza; Swastikawara, Sinta (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2010)
The lack in communication in which happen of deaf children, making deaf children uncared because of their unable in communication field as a primary tool of communication skill inÂ society. The deaf children need tuition, especially in communication field so that they can lifeÂ independent. One of formal way which is gone through deaf children by applying in school for children with special needs, because with teacher human resources that has formal ability can help deaf children to fulfill their needs in communication field. The existence of school for children with special needs for deaf children like SDLB-B YPTB Malang is one of school that focuses for deaf children.The goal from this research is to describe communication strategy that has done by teacher SDLB-B YPTB Malang in sharpening communication skill deaf student. Furthermore, the type of this research method is qualitativeÂ â case study approach. This research located in SDLB-B YPTB Malang which address at Jalan Brigjen Slamet Riadi 126 Malang. The dataâs gathering use observation and depth interview.From this research it has founded that teacher SDLB-B YPTB Malang used identification as base to make communication strategy. Communication strategy which formed interpersonal relationship and followed with learning communication for deaf student. This communication strategy is purposed to sharpening communication skill of deaf student both in sign language and verbal language. Key words: communication strategy, teacher, deaf student, communication skill.